2003
DOI: 10.1016/s0378-1097(03)00795-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer intoClostridium difficileCD630 and characterisation of its methylase genes

Abstract: Ignorance of pathogenesis in Clostridium difficile may be attributable to a lack of effective genetic tools. We have now shown that oriTbased shuttle vectors may be conjugated from Escherichia coli donors to the C. difficile strain CD630, at frequencies of around 10 36 transconjugants per donor cell. Transfer is unaffected by either sequences present on the vector or its methylation status. Whilst the genome of this strain carries five methylase genes, there is no in silico or experimental evidence for cognate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…There is little information on methylation of chromosomal DNA in C. difficile . Five methylases have been identified in C. difficile 630 [ 34 ], but in vivo methylation patterns have not been characterized. We took advantage of the pulse profiles of the Pacific Biosciences RSII reads that hold information about base modifications [ 35 , 36 ] to generate the first comprehensive analysis of methylation patterns in C. difficile (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information on methylation of chromosomal DNA in C. difficile . Five methylases have been identified in C. difficile 630 [ 34 ], but in vivo methylation patterns have not been characterized. We took advantage of the pulse profiles of the Pacific Biosciences RSII reads that hold information about base modifications [ 35 , 36 ] to generate the first comprehensive analysis of methylation patterns in C. difficile (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…m6 A modifications can be identified with high confidence and the vast majority of the these modifications (7288/7687 = 95%) were associated with the motif CAAAA A , in which the last adenine residue is modified (Figure 3 B). Previous studies identified a single methylase, M. Cdi 25 (corresponding to CD2758) with homology to adenine specific methylases, but failed to identify its target site in restriction protection experiments [ 34 ]. We postulate that CD2758 recognizes and methylates last adenine residue the CAAAAA motif and that this is possibly the only adenine-methylase in C. difficile 630Δ erm .…”
Section: Resultsmentioning
confidence: 99%
“…This is a common organization and has been used to develop site-specific integration vectors in some bacteria (19). Very few vector systems (15,16,25,28) are available for C. difficile, and construction of an integration vector using ⌽CD119 sequence information would be of considerable value for molecular and genetic research on this medically important pathogen. No ORF encoding an excisionase was identified in the ⌽CD119 genome.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the putative role of these factors in C. difficile ‐associated disease is yet to be determined, primarily because C. difficile is not amenable to genetic manipulation. At present, the only reproducible method for the introduction of recombinant DNA molecules into C. difficile is by conjugation from an Escherichia coli or Bacillus subtilis donor (Mullany et al ., 1994; Purdy et al ., 2002; Herbert et al ., 2003; Roberts et al ., 2003; Hussain et al ., 2005). Tn 916 ‐mediated conjugative transfer from B.subtilis has been used to examine the role of SigK in sporulation (Haraldsen and Sonenshein, 2003) and we have successfully used conjugative transfer of pIP404‐based E. coli–Clostridium perfringens shuttle vectors to study the effect of glucose on the regulation of toxin A and toxin B expression in an avirulent C. difficile strain background (Mani et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a native C. difficile plasmid replicon was incorporated into an E. coli–C. difficile shuttle vector, which could be introduced into C. difficile by conjugation and stably maintained (Purdy et al ., 2002; Herbert et al ., 2003). Conjugative transfer of a non‐replicative suicide plasmid has previously been used for the insertional inactivation of a metabolic gene in an avirulent strain (Liyanage et al ., 2001), although the resultant progeny were non‐viable.…”
Section: Introductionmentioning
confidence: 99%